2018
DOI: 10.1292/jvms.17-0577
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-serine modifies free amino acid composition of maternal milk and lowers the body weight of the offspring in mice

Abstract: The growth of offspring is affected not only by the protein in maternal milk but also by the free amino acids (FAAs) contained in it. L-Serine (L-Ser) is known as an important FAA for the development of the central nervous system and behavioral activity. However, it is not clear whether L-Ser is transported into the pool of FAAs contained in milk and thereby affects the growth of offspring. Using mice, the current study investigated the effects of dietary L-Ser during pregnancy and lactation on milk and plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Similar results have been confirmed about serine (Ser). In maternal milk, L-Ser levels increased by about 120 nmol/ml in mice fed the diet containing 2% L-Ser as compared to the control diet [14]. On the other hand, milk D-Ser levels in the mice fed with 0.5% D-Ser diet was over 2,000 nmol/ml higher than that in the mice fed with control diet (Aso et al, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…Similar results have been confirmed about serine (Ser). In maternal milk, L-Ser levels increased by about 120 nmol/ml in mice fed the diet containing 2% L-Ser as compared to the control diet [14]. On the other hand, milk D-Ser levels in the mice fed with 0.5% D-Ser diet was over 2,000 nmol/ml higher than that in the mice fed with control diet (Aso et al, unpublished data).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the patterns of change in free amino acid concentrations in milk were similar between WIS and WKY rats. The previous study reported that dietary L-Ser decreased body weight of offspring in mice [17]. Dietary L-Ser increased free L-Ser concentration in the milk of dams, but it did not influence free L-Ser in plasma in 13-day-old offspring.…”
Section: Discussionmentioning
confidence: 97%
“…Milk proteins are synthesized by free amino acids, peptides, proteins and glucose in plasma, and modification of the free amino acid profile in maternal plasma also influences the free amino acid profile in milk [17]. Differences in free amino acid concentrations in milk were observed between WIS and WKY rats; however, there were no significant interactions between the strains and lactation stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations